Artificial light puts ecosystem services of frugivorous bats at risk. Issue 2 (10th March 2014) - Lewanzik, Daniel; Voigt, Christian C.; Pocock, Michael
Summary Currently, tropical forests are transformed into pasture and agricultural areas at an unprecedented rate, yet converted areas are often abandoned by farmers because depleting soil fertility renders unprofitable any agricultural land use. Natural succession of abandoned land could counter the loss of biodiversity, but the rate of natural reforestation is slow. Neotropical frugivorous bats facilitate natural succession because they seem to tolerate habitat disturbance when dispersing seeds of pioneer plants. Under naturally dark conditions, bats produce a copious seed rain even in deforested habitats and connect distant forest fragments. Yet, artificial light at night may compromise bat‐mediated seed dispersal if bats avoid lit areas. This may delay or jeopardize natural forest succession in fragmented tropical landscapes. We asked whether the foraging behaviour of Sowell's short‐tailed bats Carollia sowelli, a specialist on infructescences of pepper plants (Piperaceae), is negatively affected by artificial light at night. First, in a dual choice experiment with captive bats, we demonstrate that food was less often explored and consumed in the dimly illuminated than in the dark compartment, indicating that artificial light alters the foraging behaviour of fruit‐eating bats. Secondly, using observations in free‐ranging bats, we found that infructescences were less likely to be harvested when plants were illuminated by a street lamp than under natural darkness. Synthesis and applications. Natural succession of deforested areas and connectivity of remaining forest patches may suffer due to artificial light at night through a reduction in nocturnal seed disperser activity in lit areas. This could have negative impacts on biodiversity and consequent effects on land erosion, particularly in developing countries of the tropics where light pollution increases rapidly with growing economies and human populations. Mitigation requires that the use of artificial light should be limited in space, time and intensity to the minimum necessary. The effectiveness of 'darkness corridors' to enhance fragment connectivity and to reduce species loss should be evaluated. Policy‐makers of tropical countries should become aware of the potential detrimental effects of artificial lighting on wildlife and ecosystem functioning.